The gays' and lesbians' rights in an enlarged European Union - Borrillo, Daniel (European Studies, 2006)
During the last few years, gay and lesbian rights have reached the European Union human rights agenda and different instruments to combat discrimination have been adopted, which have had major implications for the gay and lesbian communities all over Europe. This volume focuses on less known and less studied aspects of these accomplishments.